Henoch-Schönlein Purpura /IgA Vasculitis Complicated by Coronary Artery Aneurysm: A Case Report and Literature Review - Kang, Zhijuan; Wu, Wentao; Xun, Mai; Ding, Yunfeng; Li, Zhihui (Frontiers in Pediatrics, 2022)
Henoch-Schönlein purpura (HSP) is the most common form of systemic vasculitis in children and often involves the skin, gastrointestinal tract, joints, and kidneys, though cardiac involvement rarely occurs. We examined a 6-year-old male child with HSP, who had renal and cardiac involvement at the initial stage of the disease and found an extremely rare coronary artery aneurysm. After administration of glucocorticoid combined with mycophenolate mofetil, the renal involvement improved, but the coronary artery aneurysm remained. Pursuant to this case, we retrieved information on other cases of HSP complicated with cardiac involvement inform the PubMed database, and we excluded cases of cardiac involvement accompanied by Kawasaki disease, polyarteritis nodosa, rheumatic fever, and other diseases. We then analyzed gender, age, cardiac involvement, renal involvement, treatment, and. To date, 24 cases of HSP complicated with cardiac involvement have been reported. Among them, there were 22 male and 2 female patients, with the onset age ranging from 3 to 71 years old. A total of 10 children (including the child we examined) and 14 adults were identified, and 17 patients (70.8%) had HSP complicated with renal involvement. The majority of patients were treated with glucocorticoid and/or immunosuppressants or biological agents; 4 patients died (16.7%), 8 patients were completely relieved (33.3%), and 3 patients had unknown prognoses. HSP complicated with cardiac involvement may cause a poor prognosis and early treatment may be essential. Our findings reveal that glucocorticoid does not prevent the occurrence of renal and cardiac involvement in HSP patients. If HSP is complicated with coronary artery dilation, the therapeutic effect of glucocorticoid combined with immunosuppressants is not satisfactory, and early administration of biological agents may be an effective therapeutic regimen.